2018
DOI: 10.14283/jpad.2018.18
|View full text |Cite
|
Sign up to set email alerts
|

Development of Azeliragon, an Oral Small Molecule Antagonist of the Receptor for Advanced Glycation Endproducts, for the Potential Slowing of Loss of Cognition in Mild Alzheimer’s Disease

Abstract: Increasing evidence supports the role of the Receptor for Advanced Glycation Endproducts (RAGE) in the pathology of Alzheimer’s disease. Azeliragon (TTP488) is an orally bioavailable small molecule inhibitor of RAGE in Phase 3 development as a potential treatment to slow disease progression in patients mild AD. Preclinical studies in animal models of AD (tgAPPSwedish/London) have shown azeliragon to decrease Aβ plaque deposition; reduce total Aβ brain concentration while increasing plasma Aβ levels; decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 31 publications
0
54
0
3
Order By: Relevance
“…Four drugs targeting the inflammation/ infection/immunity (17.6% of all agents) are currently in phase 3 clinical trials. The first is ALZT-OP1 (cromolyn + ibuprofen) aiming to increase the clearance of Aβ by modulating the microglia activation; the next is azeliragon, a RAGE antagonist, aiming to reduce Aβ load and neuroinflammation in the brain; 371 the third is masitinib, a tyrosine kinase inhibitor, aiming to reduce the Aβ charge and tau phosphorylation; and the last is COR388, a bacterial protease inhibitor targeting gingipain, aiming to reduce neuroinflammation and hippocampal neurodegeneration. Other potential candidates did not seem to lead to conclusive results and were halted.…”
Section: Disease Modifying Treatment: Present and Futurementioning
confidence: 99%
See 1 more Smart Citation
“…Four drugs targeting the inflammation/ infection/immunity (17.6% of all agents) are currently in phase 3 clinical trials. The first is ALZT-OP1 (cromolyn + ibuprofen) aiming to increase the clearance of Aβ by modulating the microglia activation; the next is azeliragon, a RAGE antagonist, aiming to reduce Aβ load and neuroinflammation in the brain; 371 the third is masitinib, a tyrosine kinase inhibitor, aiming to reduce the Aβ charge and tau phosphorylation; and the last is COR388, a bacterial protease inhibitor targeting gingipain, aiming to reduce neuroinflammation and hippocampal neurodegeneration. Other potential candidates did not seem to lead to conclusive results and were halted.…”
Section: Disease Modifying Treatment: Present and Futurementioning
confidence: 99%
“…For the sake of brevity, we will not explain the method in great detail but rather refer the reader to our recent article that gives an insight of TDA and how it can be applied to high-dimensional and multiscale data. 371 However, in brief, TDA extracts topological and geometrical features that persist across spatial scales (hence beyond classical network analysis). These persistent features correspond to invariances of the data and are summarized in specific diagrams as shown in Figure 1 (right panel, A and B).…”
Section: Ways To Find New Treatments For Ad: What Could Help To Accelerate the Dmt Discovery?mentioning
confidence: 99%
“…However, contradictory findings have been published and other studies have shown that RAGE inhibition, elicited either through genetic deletion or through the use of anti-RAGE or anti-HMGB1 antibodies, was associated with unchanged or decreased bacterial dissemination 17,38,39 . Indeed, although trials in patients with mild Alzheimer's disease did not support clinical efficacy of azeliragon (TTP448, vTv Therapeutics, High Point, NC, USA), an inhibitor of RAGE-amyloid β protein interactions, no obvious safety issues were associated with its use (5 mg orally once daily for 18 months) in human patients [40][41][42] . Future research should therefore investigate the extent to which our current findings might translate to the treatment of critically ill patients with ARDS in terms of the timing, dosing and methods of administration of RAGE inhibition candidates, with a focus on their efficacy and safety profiles.…”
Section: Discussionmentioning
confidence: 99%
“…RAGE is over expressed in the brain tissues of AD patients. Azeliragon has been shown to slow down the progression of AD [ 118 ]. It was developed by vTv Therapeutics® (Originator) and was studied in the phase 3 clinical trials for the treatment of Alzheimer’s type dementia (STEADFAST).…”
Section: Therapeutic Strategies For the Development Of Anti-ad Drugsmentioning
confidence: 99%